2019
DOI: 10.1108/md-09-2018-1070
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy in the manufacturing sector: benefits, opportunities and barriers

Abstract: In recent years, Circular Economy (CE) has come to prominence as an alternative to the classic approach of "make-use-dispose". How companies can exploit the opportunities of CE to position themselves better are not well articulated in literature. This paper therefore aims to identify the barriers and opportunities of CE in the manufacturing sector through a socio-political, economic, legal and environmental perspective. Design/methodology/approach: The study adopts a positivist approach, which is deductive in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 253 publications
(260 citation statements)
references
References 50 publications
4
156
0
17
Order By: Relevance
“…SA8000 is also becoming popular for supplier selection (Malesios et al, ). There are several articles (Lee, ; Kumar et al, ) on green procurement that study the role of sourcing and inbound logistics in achieving sustainability (Blome, Hollos, & Paulraj, ; Testa, Annunziata, Iraldo, & Frey, ). Therefore, for a group of SMEs in a specific region deriving the relationship of take and sustainability performance reveals the current state of CE practices.…”
Section: Analytical Framework For This Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…SA8000 is also becoming popular for supplier selection (Malesios et al, ). There are several articles (Lee, ; Kumar et al, ) on green procurement that study the role of sourcing and inbound logistics in achieving sustainability (Blome, Hollos, & Paulraj, ; Testa, Annunziata, Iraldo, & Frey, ). Therefore, for a group of SMEs in a specific region deriving the relationship of take and sustainability performance reveals the current state of CE practices.…”
Section: Analytical Framework For This Researchmentioning
confidence: 99%
“…CE is a concept widely studied in China and the European Union (EU), the adoption of the latter driven by legislation, but there is a big scope for analysis beyond those countries (Katz‐Gerro, Greenspan, Handy, & Lee, ; Zhu et al, ). Moreover, although there is research in larger organisations (Kumar, Sezersan, Garza‐Reyes, Gonzalez, & Al‐Shboul, ; Zhu et al, ), study on SMEs adoption of CE is scant. Only recently, research has been undertaken to facilitate implementation of CE in SMEs covering awareness, strategies, policy, barriers and challenges, benefits, and business models.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CE involves a high degree of complexity as it encompasses all activities from extraction to production and beyond (Ghisellini, et al, 2016). Moreover, CE is an economy that aims to keep the value and utility of components, materials and products at their highest by creating the regenerative and restorative design (Howard, et al, 2018;Kumar, et al, 2018).…”
Section: Literature Review 21 Circular Economy and Supply Chain: Cirmentioning
confidence: 99%
“…However, due to the immaturity of the proposed measures, firms still mostly operate under the linear approach, rather than the CE model. Evidence shows that while governments and international institutions have understood the importance of CE and have made efforts towards promoting its implementation, those efforts are lacklustre, so far, and a lot more work needs to be put in them if firms are to abandon linear and adopt the CE approach (Kumar et al, 2019;Tam, Soulliere, & Sawyer-Beaulieu, 2019).…”
Section: Literature Review 21 Linear and The 3r's Principlesmentioning
confidence: 99%
“…Unarguably, the implementation of CE holds several benefits impacting environmental and economic strategies (Yuan, et al, 2006;Kumar et al, 2019). Yuan, et al (2006) and Zhijun & Nailing (2007) report that the Chinese Government has identified three steps/levels that needed to be put into action towards a successful and effective implementation of a CE.…”
Section: Ce Applications and Limitation Factorsmentioning
confidence: 99%